Research On Target And Path Planning Of Regional Carbon Peaking And Carbon Neutrality - Yang, Fan (International Journal of Global Economics and Management, 2024)
To achieve peak carbon neutrality is a broad and profound economic and social systemic change. At present, the economic and social development of our country has entered the stage of accelerating green and low-carbon high-quality development. In this paper, under no less than three scenarios, the regional dual carbon target is associated with the time node of carbon peak and carbon neutrality, and is associated with the improvement of energy efficiency and the increase of the proportion of non-fossil energy consumption. In various scenarios, if the GDP in 2035 doubles over the base period and quadruples in 2060, the method of calculating carbon emissions is found. If the carbon absorption amount of ecological carbon sink in 2060 is 10% of the carbon emissions of the base period, the calculation method of carbon emissions at this time is found; To find the targets and paths that can determine the GDP, population, energy consumption, energy efficiency and non-fossil energy consumption in 2025, 2030, 2035, 2050 and 2060, and finally complete the qualitative and quantitative analysis of the four major projects.